Entre Proteção e Máscaras: Crítica(s) do direito / Between Protection and masks: Critique(s) of law - Buckel, Sonja (Revista Direito e Práxis, 2019)
DOI: 10.1590/2179-8966/2019/46049 Resumo O texto apresenta uma análise das possibilidades de intervenção estratégica do direito por movimentos sociais a partir da discussão de críticas à forma jurídica nas tradições marxista, pós-estruturalista, feminista, queer e da Teoria Crítica. Retoma a reconstrução de uma teoria materialista do direito conforme desenvolvida pela autora no livro Subjektivierung und Kohäsion. Zur Rekonstruktion einer materialistischen Theorie des Rechts, ainda sem tradução para o português (resumo pela tradutora). Palavras-chave: Teoria materialista do direito; Movimentos sociais; Hegemonia; Lutas por direito. Abstract The text presents an analysis of the possibilities of strategic intervention using the law by social movements based on the discussion of critiques of the legal form in the Marxist tradition, in the Critical Theory, post-structuralism, and feminist and queer legal debates. It resumes the reconstruction of a materialist theory of law as developed by the author in the book Subjektivierung und Kohäsion. Zur Rekonstruktion einer materialistischen Theorie des Rechts, which was not yet translated into Portuguese (abstract by the translation). Keywords: Materialist theory of law; Social movements; Hegemony; Struggles for rights.